2010
DOI: 10.1016/j.virol.2010.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Replication competent molecular clones of HIV-1 expressing Renilla luciferase facilitate the analysis of antibody inhibition in PBMC

Abstract: Effective vaccine development for human immunodeficiency virus type 1 (HIV-1) will require assays that ascertain the capacity of vaccine immunogens to elicit neutralizing antibodies (NAb) to diverse HIV-1 strains. To facilitate NAb assessment in peripheral blood mononuclear cell (PBMC)-based assays, we developed an assay-adaptable platform based on a Renilla luciferase (LucR) expressing HIV-1 proviral backbone. LucR was inserted into pNL4-3 DNA, preserving all viral open reading frames. The proviral genome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
247
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 173 publications
(260 citation statements)
references
References 71 publications
(100 reference statements)
11
247
0
Order By: Relevance
“…This experiment was considered pertinent because TZM-bl cells express ∼2-to 10-fold more CD4 molecules than primary CD4 + T cells (37,38), which could influence their activity. Thus, we tested PG9-iMab against a subset (n = 23) of the 118 strains previously tested in the TZM-bl/pseudovirus assay, using replication-competent reporter (Env-IMC-LucR) viruses in a PBMC neutralization assay (39). This subset of viruses was shown to be representative of the full panel of HIV-1 strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This experiment was considered pertinent because TZM-bl cells express ∼2-to 10-fold more CD4 molecules than primary CD4 + T cells (37,38), which could influence their activity. Thus, we tested PG9-iMab against a subset (n = 23) of the 118 strains previously tested in the TZM-bl/pseudovirus assay, using replication-competent reporter (Env-IMC-LucR) viruses in a PBMC neutralization assay (39). This subset of viruses was shown to be representative of the full panel of HIV-1 strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3,27-31 However, we found that these EMCV IRES-containing reporter viruses vastly overexpress Nef 8 and exhibit both poor replication and stability of the reporter gene (personal observations and Brown et al 29 ). To overcome these challenges, we explored replication-competent HIV-1 reporter viruses that utilized the small ''ribosome skipping'' T2A peptide (18 amino acids) to mediate Nef expression in frame with, and release from (via ribosome skipping of the last peptide bond at the C-terminus of the T2A peptide 32,33 ), LucR.…”
mentioning
confidence: 97%
“…of protection-encompassing proviral infectious molecular clones (IMC) of transmitter/founder (T/F) HIV-1 [4][5][6] and several forms of reporter virus derivatives expressing genes such as enhanced green fluorescent protein (EGFP) 7 and Renilla luciferase (LucR), 4,8 which underpin new immune monitoring assays and augment the performance of existing assays for various vaccine discovery approaches. 3,4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Among formerly described replication-competent HIV-1 reporter vectors were those designed with a bicistronic EGFP-IRES-nef cassette in place of nef, in which the EGFP gene is downstream of env, and nef is under translational control of an internal ribosome entry site (IRES) from encephalomyocarditis virus (EMCV).…”
mentioning
confidence: 99%
See 2 more Smart Citations